Hubungan Pengetahuan Ibu Dengan Pemberian Air Susu Ibu (ASI) Eksklusif di Wilayah Kerja Praktek Mandiri Bidan (PMB) Siti Saleha S.Tr. Keb Desa Bantaianriau Tahun 2023 - Wilda Tiara; Vitalia Hanako Murni Simanjuntak; Sonia Novita Sari; Markus Doddy Simanjuntak; Deby Cyntia Yun (Student Research Journal, 2023)
One of the efforts made to reduce MMR is the Antenatal Care (ANC) examination program which is mandatory for pregnant women. The Indonesian Ministry of Health stipulates that examinations for pregnant women or antenatal care be carried out at least 6 times over 9 months. The aim of this research was to determine the relationship between maternal knowledge and breastfeeding in the Independent Practice work area of ​​Midwife Siti Saleha, Bantaian Village, Riau. This research uses an analytical observational design using quantitative methods with a cross-sectional research design approach. The number of samples in this study was 28 respondents. The conclusion of this research is that there is a relationship between maternal knowledge and breastfeeding. It is recommended that mothers do not blindly accept advertisements about formula milk in electronic media and the internet, mothers should ask health workers to find out more about the benefits and contents of breast milk which are no less than those contained in formula milk.